POTENSI DAN DAMPAK PERBANKAN TERSEDENTRALISASI (DEFI) TERHADAP INKLUSI KEUANGAN: STUDI LITERATUR - Tehedi Tehedi; Devi Trenggani (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to examine the potential and impact of decentralised finance (DeFi) on financial inclusion through a literature review. DeFi is a blockchain-based innovation that offers financial services without intermediaries, thereby potentially expanding financial access for the unbanked and underbanked. The findings indicate that DeFi can enhance financial inclusion through cost efficiency, transparency, and ease of access to digital financial services. However, on the other hand, DeFi also presents challenges such as security risks, digital asset volatility, digital literacy gaps, and insufficient regulation and consumer protection. Therefore, optimising the benefits of DeFi for financial inclusion requires synergy between technological innovation, public education, and regulatory strengthening so that its benefits can be felt evenly and sustainably.